2016
DOI: 10.1039/c6tb02086k
|View full text |Cite
|
Sign up to set email alerts
|

Graphene and graphene-based nanocomposites: biomedical applications and biosafety

Abstract: Graphene is the first carbon-based two dimensional atomic crystal and has gained much attention since its discovery by Geim and co-workers in 2004.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
106
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(106 citation statements)
references
References 136 publications
0
106
0
Order By: Relevance
“…Both materials contain functional groups on their surfaces which improve their hydrophilic properties, and they can be further functionalized to tailor their properties for intended purposes. On the other hand, the lipophilicity of GR can be used in membrane barrier penetration systems [9].…”
Section: Introductionmentioning
confidence: 99%
“…Both materials contain functional groups on their surfaces which improve their hydrophilic properties, and they can be further functionalized to tailor their properties for intended purposes. On the other hand, the lipophilicity of GR can be used in membrane barrier penetration systems [9].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, graphene is used as nanoscale building blocks for new nanocomposites because of its unique properties [12][13][14]. Recent research showed that magnetic nanoparticles (MNPs) could be attached to graphene, which can be applied in magnetic resonance imaging [15], targeted drug delivery [16,17], biocompatible adsorbent [18], magnetic solid phase extraction [19], microwave electromagnetic [20], Schottky diode applications [21], and biomolecule immobilization [22].…”
Section: Introductionmentioning
confidence: 99%
“…This very specific property along with the other interesting physiochemical features of carbon nanomaterials (CNMs) have ushered in a new biomedical era. In addition to their early medical applications in biosensors and bioimaging contrast agents, recently, a series of studies have been published on CNMs‐based advancements in regenerative medicine, tissue engineering, drug delivery, and nonviral gene transfer (Alshehri et al, ; Georgakilas et al, ; G. Hong, Diao, Antaris, & Dai, ; J. Lee, Kim, Kim, & Min, ; Pattnaik, Swain, & Lin, ; Zheng, Ananthanarayanan, Luo, & Chen, ). Despite these beneficial contributions, the potential applications of CNMs have not been expanded to the clinical trial stage as yet.…”
Section: Introductionmentioning
confidence: 99%